(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1943)
The hoard consists of eight socketed axes, two leaf-shaped swords, seven spearheads, and a corrugated bronze tube. All the objects were covered with a beautiful patina, but they were deeply corroded and broken. It seems almost certain that all the objects, save perhaps the swords, were already damaged before their deposition in the earth; the hoard in fact belongs to the class, so common in the Late Bronze Age, known as founders’ hoards. The axes are all of distinctly Irish type. The hoard represents the first accurately located Late Bronze Age objects, to be reported from the eastern shore of Loch Fyne.